Sexual satisfaction and sexual distress after cancer: The role of body image disruption, self‐compassion, sexual pain and relationship satisfaction. Issue 11 (13th July 2021) - Michael, Sarah; Skaczkowski, Gemma; Wilson, Carlene
Abstract: Objective: To identify variables that correlate with sexual satisfaction and sexual distress among adult cancer survivors, and how these differ, providing a basis from which approaches to intervention may be identified. This study examined four key variables: body image disruption, self‐compassion, relationship satisfaction and sexual pain, previously all linked to sexual quality of life. Methods: A cross‐sectional survey was conducted online, with participants ( n  = 113) recruited via cancer charities, support groups and sexual counsellors' networks. A multivariate multiple regression analysis was conducted to analyse relationships among variables. Results: In a regression adjusted for age, sex and time since diagnosis, higher sexual distress was significantly associated with higher body image disruption ( β  = 0.23; p  = 0.024), lower self‐compassion ( β  = −0.29; p  = 0.009) and higher sexual pain ( β  = 0.39; p  < 0.001); but not relationship satisfaction ( β  = −0.08; p  = 0.434). Higher sexual satisfaction was significantly associated with higher relationship satisfaction ( β  = 0.35; p  = 0.002) and lower sexual pain ( β  = −0.29; p  = 0.005), but not body image disruption ( β  = −0.19; p  = 0.089), or self‐compassion ( β  = 0.06; p  = 0.614). Sexual pain had a significantly stronger association with sexual distress than sexual satisfaction; F (1, 84) = 18.29, p  < 0.001. Conclusions: Sexual distress and sexual satisfaction are associated with different psycho‐social correlates even though both are used as indicators of sexual health. Research should seek to further understand the differences in these two critical markers of sexual health, with these differences likely to highlight the need to match interventions to the nature of the sexual difficulties experienced following cancer treatment.